ANALYSIS OF MATHEMATICAL PROBLEM WITH GROUP WISE FOR COMPUTERIZED ADAPTIVE TESTING - Rukli Rukli (Universitas Negeri Makassar, 2018)
This study aims to put the parameters of the problem on a general scale with a group wise design. Placement of questions on a general scale can be interpreted that although the test participants responded to the character of the problem is not the same but the ability of test participants in Competitive Adaptive Testing (CAT) can be compared with each other. Data response question comes from four packages namely package 1, package 2, and package 3 National Exam on mathematics subjects. The total number of questions is 140. The data is analyzed with the Bilog_MG program. The results show that the number of questions meet the Rasch model of 109 questions. The matter can be entered into CAT bank. Although the test participants responded to the problem and the number of questions was not the same but the test scores were comparable